Investment equilibrium of an integrated multi–stakeholder electricity–gas–hydrogen system. (October 2021) - Pan, Guangsheng; Gu, Wei; Chen, Sheng; Lu, Yuping; Zhou, Suyang; Wei, Zhinong
Abstract: The coordinated planning and operation of electric power and natural gas systems contribute significantly toward the integration of renewables and decarbonization of energy systems. The coupling between the two systems will be further increased due to the potential use of hydrogen that represents an indispensable terminal energy source. Thus, this study proposes an investment equilibrium model for an integrated electricity–gas–hydrogen system (IEGHS) constituting electric power systems, natural gas systems, and hydrogen fuel stations. Specifically, electricity, gas, and hydrogen energy trading are considered in this model. A triangular coupling relationship is formulated in the IEGHS with the objective of maximizing each stakeholder's profit. Furthermore, two trading mechanisms with different energy prices are built and compared. In particular, the equilibrium model with locational marginal energy prices (LMEPs)-based trading is further solved via a direct approach based on the Karush–Kuhn–Tucker conditions and strong-duality theory. Case studies indicate that the LMEP-based trading provides the highest overall benefit in the case of multiple stakeholders. Additionally, the impact of energy price, investment equipment price, and equipment conversion efficiency on the investment equilibrium of IEGHS is investigated. Highlights: An integrated closed-loop multi-stakeholder electricity-gas-hydrogen system is developed. Two different cooperation mechanisms with multi-stakeholders are established. A direct approach is developed to solve the investment equilibrium model. The investment equilibrium of the system in 2020, 2030, and 2050 is analyzed.